Geomorphology, first 36Cl datings and chrono-evolutionary model of Mount Aragats paleoglaciers (Armenia) - Carrasco, R. M.; Fernandez-Lozano, J.; Karampaglidis, T.; Soteres, R. L.; Braucher, R.; Gairoard, S.; Petrosyan, A.; Nahapetyan, S.; Arakelyan, D.; Pedraza, J.; Gasparyan, B.; Aumaitre, G.; et al. (My University, 2025)
Mount Aragats is one of the largest glaciated volcanoes of the Armenian Highlands (Rwlllwllwb lbnbwZruwnh) and culminating in the Aragats Peak, the highest peak of the Republic of Armenia (4090 masl). Here, prehistoric societies have been present for millennia, so assessing the local influence of past glaciations is a crucial factor to better understand the cultural evolution of this region. Therefore, this work focuses on a detailed study of the morphology and morphostratigraphic succession of Mount Aragats paleoglaciers. Geomorphic-based paleoglacier reconstruction along 36Cl cosmogenic dating (n = 13) of moraines reveal that during the Middle and Upper Pleistocene, a plateau glacier featuring ice lobes covered this area, featuring outlet lobes reaching up to 17 km in length, thicknesses of up to 350 m and descending to 2040 masl. According to the morphostratigraphic succession of ice-marginal features, absolute chronologies and regional correlations, the chronoevolutionary sequence of these glaciers comprises three intervals: (1) The absolute Maximum Ice Extent or Aragats Glacial Maximum occurred during the Penultimate Glacial Cycle within the MIS6e (c. 180 ka). (2) Subsequently, during the Last Glacial Cycle, the Maximum Ice Extent occurred during the MIS5d (c. 111 ka) followed by two secondary glacial maxima stabilizations during the MIS3a (c. 37 ka) and the MIS2 (c. 17 ka). Finally, (3) the Post-Glacial Period (PCP, Holocene, MIS1). The disappearance of the glaciers on Mount Aragats was established at the beginning of the second half of the 20th century by direct observations. The current morphodynamic environment corresponds to active rock glaciers, some ne<acute accent>ve` moraines and widespread activity of slope processes such as debris flow and debris slides.
Keywords: glaciovolcanic morphology; aragats mountain; 36cl-cre dating; penultimate glacial cycle; last glacial cycle; armenian highlands